Women, crusading and the Holy Land in historical narrative - Hodgson, Natasha R. (Warfare in history., 2007)
"This book compares perceptions of women from a wide range of historical narratives including those eyewitness accounts, lay histories, and monastic chronicles that pertained to major crusade expeditions and the settler society in the Holy Land. It addresses how authors used events involving women and stereotypes based on gender, family role, and social status in writing their histories: how they blended historia and fabula, speculated on women's motivations, and occasionally granted them a literary foice in order to connect with their audience, impart moral advice, and justify the crusade ideal"--Jacket